The Effect of Motivation on Employee Performance: in Case of Different Companies - Nasibli, Ibrahim (Annals of Spiru Haret University. Economic Series, 2021)
With the abandonment of the classical management approach and the adoption of the modern management approach in the enterprises, it has been emphasized by the managers that the workforce is as important as the technology for the success of the business. The prominence of people in businesses has led to the creation of the human resources department and, accordingly, the emergence of many systems that direct people and increase their productivity. At the beginning of these systems is the motivation and performance evaluation system. It is very difficult to keep employees in the company for a long time and encourage them to act in favour of the company. The main purpose of motivation methods is to ensure that employees act in accordance with the company’s goals and achieve successful results. The purpose of the study was to determine whether the factors influencing the performance of employees and employers were rewarding factors, additional payment factors or psycho-social factors, and whether these factors were age, gender, marital status, education level, work experience, occupation, etc. is to investigate how it differs according to demographic factors.